Developing Pocketbook Media to Enhance Students' Vocabulary Mastery and Pronunciation Accuracy in English for Business Course - Andriani, Fenty; Febrilyantri , Candra; Sajjadi , Seyyed Abbas (Institut Agama Islam Negeri Madura, 2025)
Due to limited familiarity with business terminology and challenges to connect the right letter-sound correspondences, a lot of students attending English for Business course encounter difficulties in both verbal and written communication. This is definitely a critical issue to be paid more attention as students’ language proficiency will lead to the success in achieving learning objectives and workplace expectations. Though some previous studies regarding the development of pocketbooks have been conducted, none has focused on the business English context. Therefore, this study aims to address this study gap by investigating the development of Business English pocketbook, specifically focusing on vocabulary mastery and pronunciation accuracy to meet the educational objectives and workplace demands. This pocketbook was developed based on the ADDIE model, which consists of five phases including Analysis, Design, Development, Implementation, and Evaluation. This study highlights the valuable assistance of ADDIE framework in developing a well-organized pocketbook to boost vocabulary mastery and pronunciation accuracy for business English needs.